Establishing the yeast Kluyveromyces lactis as an expression host for production of the saposin-like domain of the aspartic protease cirsin - Curto, Pedro (2014)
Typical plant aspartic protease zymogens comprise a characteristic and plant specific insert (PSI). PSI domains can interact with membranes and a role as defensive weapon against pathogens has been proposed. However, the potential of PSIs as antimicrobial agents has not been fully investigated and explored yet, due to existing problems in producing sufficient amounts of these domains in bacteria. Here, we report the development of an expression platform for the production of the PSI domain of cirsin in the Generally Regarded as Safe (GRAS) yeast Kluyveromyces lactis. We successfully generated K. lactis transformants expressing and secreting significant amounts of correctly processed and glycosylated PSI as well as its non-glycosylated mutant. A purification protocol was established with protein yields of ∼4.0 mg/L for both wild-type and non-glycosylated PSI which represents the highest reported yield for a non-tagged PSI domain. Subsequent bioactivity assays targeting phytopathogenic fungi indicated that the PSI of cirsin is produced in a biologically active form in K. lactis and provided clear evidence for its anti-fungal activity. This yeast expression system thereby emerges as a promising production platform for further exploring the biotechnological potential of these plant saposin-like proteins.